Nitrogen removal during secondary treatment by aquatic systems - Nalbur, BE; Akça, L; Bayhan, H (IWA PUBLISHING, 2003)
Within the context of this study, two lab-scale aquatic plant reactors consisting of duckweed (Lemna minor) ponds, were investigated for the removal of nitrogen forms during the secondary treatment of domestic wastewater. TKN, NH3-N and NO3-N parameters have been measured in both reactors for hydraulic retention times ranging from 3.3 days to 23 days and at various distances from the inlet of reactors. The results were evaluated for hydraulic retention times, hydraulic loading rates and mass loading rates. It was concluded that hydraulic and mass loading parameters were more meaningful than hydraulic retention time. Optimum nitrogen removal values of hydraulic loading rate and mass loading rate were found to be 1.2 cm/day and 90-160 mg TKN/m(2)-day, respectively. At the higher and lower loading rates, nitrogen removal efficiency was lower than those at optimum conditions. Effluent TKN concentration was around 2.5 to 3.0 mg/l while NH3-N concentration was almost zero at these loading conditions. On the other hand, effluent NO3-N concentrations changed between 7 mg/l to 11 mg/l. When investigating the longitudinal profile, values were reduced rapidly along the reactors. It was concluded that most of the nitrogen conversion occurred at the beginning of the reactor.
Keywords: aquatic ponds; duckweed; nitrogen removal; WATER TREATMENT SYSTEMS; Engineering; Environmental Sciences & Ecology; Water Resources